REFLEKSI MAULID NABI MUHAMMAD DI SEKOLAH TINGGI AGAMA ISLAM SANGATTA: MENGUATKAN AKHLAK DAN ILMU - Abdul Basir, Muchammad; Imron Ghozali; Hartono; Imrona Hayati; Muhammad; Eko Nursalim; Firdaus; Fitriyani; Fakhrurrazi (El-Madaniyah : Jurnal Pengabdian Masyarakat, 2025)
The commemoration of the Prophet Muhammad's birthday at the Sangatta Islamic College was an important moment to strengthen morals and knowledge among the academic community, especially in facing the challenges of the era of information disruption 5.0. This activity aimed to instill religious spiritual values through motivational lectures that inspired students to emulate the Prophet's morals in their daily lives, especially on campus. The research used a qualitative method with a descriptive approach, involving participatory observation, in-depth interviews, and documentation during the implementation of the activity. The results showed that participants understood the concept of morals as part of the practice of religious spiritual values and had a strong motivation to apply them in campus life. The positive responses and enthusiasm of the participants marked the success of this activity in strengthening the character and intellect of students. Therefore, it is recommended that various stakeholders collaborate to promote character development programs through similar activities on an ongoing basis, with an emphasis on strengthening spiritual intelligence (SQ) as the key to preparing an excellent young generation ready to face the dynamics of the era of information disruption.